Normal Pregnancy Is Associated with Changes in Central Hemodynamics and Enhanced Recruitable, but Not Resting, Endothelial Function - Torrado, Juan; Zócalo, Yanina; Farro, Ignacio; Farro, Federico; Sosa, Claudio; Scasso, Santiago; Alonso, Justo; Bia, Daniel (International Journal of Reproductive Medicine, 2015)
Introduction. Flow-mediated dilation (FMD), low flow-mediated constriction (L-FMC), and reactive hyperemia-related changes in carotid-to-radial pulse wave velocity (ΔPWVcr%) could offer complementary information about both “recruitability” and “resting” endothelial function (EF). Carotid-to-femoral pulse wave velocity (PWVcf) and pulse wave analysis-derived parameters (i.e., AIx@75) are the gold standard methods for noninvasive evaluation of aortic stiffness and central hemodynamics. If healthy pregnancy is associated with both changes in resting and recruitable EF, as well as in several arterial parameters, it remains unknown and/or controversial. Objectives. To simultaneously and noninvasively assess in healthy pregnant (HP) and nonpregnant (NP) women central parameters in conjunction with “basal and recruitable” EF, employing new complementary approaches. Methods. HP (n=11, 34.2 ± 3.3 weeks of gestation) and age- and cardiovascular risk factors-matched NP (n=22) were included. Aortic blood pressure (BP), AIx@75, PWVcf, common carotid stiffness, and intima-media thickness, as well as FMD, L-FMC, and ΔPWVcr %, were measured. Results. Aortic BP, stiffness, and AIx@75 were reduced in HP. ΔPWVcr% and FMD were enhanced in HP in comparison to NP. No differences were found in L-FMC between groups. Conclusion. HP is associated with reduced aortic stiffness, central BP, wave reflections, and enhanced recruitable, but not resting, EF.